Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1093/carcin/17.7.1403
|View full text |Cite
|
Sign up to set email alerts
|

CANCER BIOLOGY: Reversibility of promoter induced hepatic focal lesion growth in mice

Abstract: The effect of cessation of phenobarbital and dieldren treatment on hepatic focal lesion growth in male B6C3F1 mice was investigated. Following induction of lesions by diethylnitrosamine, mice were placed on control NIH-07 diet (control diet) or NIH-07 diet containing either dieldrin (10.0 mg/kg diet) or phenobarbital (500 mg/kg diet). Mice were sacrificed after 30 and 60 days of dietary treatment. Two additional groups of mice were fed either the dieldren- or phenobarbital-containing diet for 30 days followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…Studies of DDT and dieldrin on liver-promoting/hepatocarcinogenic actions show a strong correlation affecting gap junction-mediated intercellular communication in mice and rats liver tumors. In mice fed a diet of 10.0 mg/kg of dieldrin for 30 and 60 days, the number and volume of focal liver lesions and eosinophilic lesions increased as dieldrin was continued in the diet and subsided as dieldrin was removed (120).…”
Section: Accumulation Transformation Eliminationmentioning
confidence: 98%
“…Studies of DDT and dieldrin on liver-promoting/hepatocarcinogenic actions show a strong correlation affecting gap junction-mediated intercellular communication in mice and rats liver tumors. In mice fed a diet of 10.0 mg/kg of dieldrin for 30 and 60 days, the number and volume of focal liver lesions and eosinophilic lesions increased as dieldrin was continued in the diet and subsided as dieldrin was removed (120).…”
Section: Accumulation Transformation Eliminationmentioning
confidence: 98%
“…This agent reflects glucose metabolism in organs and tissues and thereby is widely used in tumor diagnosis, staging, curative effect determination, and recurrence monitoring (2). However, some metabolically active tissues or lesions, including the myocardium, brain tissue, inflammatory areas, and certain benign tumors, may also exhibit increased uptake of imaging agents, leading to poor 18 F-FDG imaging specificity (2). Previous preclinical and clinical studies have shown that F-18-fluoro-3'-deoxy-3'-L-fluorothymidine ( 18 F-FLT), which is a pyrimidine analogue, reflects changes in the tumor cell proliferative activity and its uptake in tumor tissues is associated with this activity (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous preclinical and clinical studies have shown that F-18-fluoro-3'-deoxy-3'-L-fluorothymidine ( 18 F-FLT), which is a pyrimidine analogue, reflects changes in the tumor cell proliferative activity and its uptake in tumor tissues is associated with this activity (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Therefore, 18 F-FLT may be used as a positron imaging agent for early evaluation of the curative effects of therapies on tumors. However, some studies have indicated that there may not be an association between 18 F-FLT uptake and tumor cell proliferative activity (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations